The Effect of a Creative-Problem Solving Learning Model Based on an Open-Ended Approach Toward High Level of Mathematical Thinking Ability of Students - Syilvia Septiani; Hidayati, Kana (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2024)
Abstract:Twenty-first-century learning focuses on developing students' mathematical thinking skills. This study examines the impact of the Creative Problem Solving (CPS) model using an Open-Ended approach to creative thinking, mathematical communication, and adversity quotient. The research employs a quasi-experimental design with a pretest-posttest non-equivalent control group at a junior high school in Bukittinggi, Indonesia. Instruments used include tests for creative thinking skills, mathematical communication, and a questionnaire for adversity quotient. Analysis was conducted using Hotelling’s T2 and univariate tests, revealing that the CPS model positively influences all three abilities.   Abstrak:Pembelajaran abad kedua puluh satu fokus pada pengembangan kemampuan berpikir matematis siswa. Penelitian ini mengkaji pengaruh model Creative Problem Solving (CPS) dengan pendekatan Open-Ended terhadap kemampuan berpikir kreatif, komunikasi matematis, dan adversity quotient. Penelitian ini menggunakan desain quasi eksperimen pretest-posttest non-equivalent control group di SMP di Bukittinggi, Indonesia, instrumen yang digunakan meliputi tes kemampuan berpikir kreatif, tes komunikasi matematis, dan angket adversity quotient. Analisis dilakukan menggunakan Hotelling’s T2 dan uji univariat, dengan hasil yang menunjukkan bahwa model CPS berpengaruh positif terhadap ketiga kemampuan tersebut.